Study on enhancing AIoT computational thinking skills by plot image-based VR. Issue 3 (3rd April 2021) - Lai, Ying-Hsun; Chen, Shih-Yeh; Lai, Chin-Feng; Chang, Yao-Chung; Su, Yu-Sheng
ABSTRACT: Due to their applications on varied and complex issues, Artificial Intelligence (AI) and Internet of Things (IoT) (collectively, AIoT) have become popular new-generation courses, but the learning of such courses needs to consider actual situations and to analyze complicated problems, making it difficult for students to improve their academic performance. The concept of computational thinking education is to allow students to find solutions to problems in different fields by understanding the problems and analyzing solution steps. In this study, we integrate the concept of computational thinking education into a course on plot image-based virtual reality (VR). It combined shooting of the actual field, instructions on the movie required to be shot, and VR in order to enable students to get immersed in thinking about problems and understanding the actual field through plot image-based VR, further plan to learn the essence of problems, and develop possible solutions. Through experimental results of experimental and control groups, we found that plot image-based VR can effectively improve students' interests in learning and computational thinking.